eshboyev COMMUNICATIVE COMPETENCE IS THE WAY OF PERSONAL SUCCESS, COMPETITIVENESS, HIGH PROFESSIONAL TRAINING: COMMUNICATIVE COMPETENCE IS THE WAY OF PERSONAL SUCCESS, COMPETITIVENESS, HIGH PROFESSIONAL TRAINING - Eshboev, Eshboev (Журнал иностранных языков и лингвистики, 2022)
this article focuses on the development of communicative competence of students in the educational process, the role of pedagogy and pedagogy in this regard.